IMPLEMENTASI PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERDESAAN (Studi di Kecamatan Secanggang Kabupaten Langkat Provinsi Sumatera Utara) - Tomi Razalie (PERSPEKTIF, 2015)
This study aims to describe how the implementation of the National Program for Community Empowerment in Rural Secanggang, Langkat, to determine the factors that affect the process of implementation of the National Program for Community Empowerment in Rural Areas in Secanggang, Langkat. The method used is descriptive qualitative research method. This study uses four key informants and 9 the key informants. Data collected by using primary and secondary data collection, and data analysis techniques performed by the analysis of qualitative data. The results showed that the PNPM Rural in Secanggang, Langkat provide benefits for people, especially women namely the increasing standard of living of families with the help of infarstruktur rural development and venture capital for women, but in implementation of the program does not run properly.